Applied video processing in surveillance and monitoring systems - Dey, Nilanjan 1984-; Ashour, Amira 1975-; Acharjee, Suvojit 1989- (Advances in multimedia and interactive technology (AMIT) book series, 2017)
This book investigates emergent techniques in video and image processing by evaluating such topics as segmentation, noise elimination, encryption, and classification, featuring real-time applications, empirical research, and vital frameworks within the field